PENGARUH KOMPETENSI, INDEPENDENSI DAN SKEPTISME PROFESIONAL AUDITOR TERHADAP KUALITAS AUDIT PADA AUDITOR PEMERINTAH DI KABUPATEN ACEH UTARA - Mukhlisul Muzahid (Politeknik Negeri Lhokseumawe, 2019)
The purpose of this study is to empirically examine the effect of competence, independence and professional auditor skepticism on audit quality in government auditors in North Aceh district. The analytical tool of this research is used the multiple regression analysis technique. This model will answer the problem there, namely measuring how much influence the influence of competence, independence and professional skepticism of the auditor on audit quality simultaneously or partially on government auditors in North Aceh district. The intended respondents were government auditors who worked at the North Aceh district Inspectorate office, totaling 21 respondents, because they had the ability to audit government agencies / offices. The data sources used in this study are primary data in the form of questionnaires and secondary data in the form of interviews. The results of the study showed that simultaneously the competence, independence and professional skepticism of the auditor had an effect on audit quality, and partially the competence and professional skepticism of the auditor had a positive effect on the quality of financial report audits in North Aceh district. The results of this study are expected to be a reference and consideration for local governments in order to improve the quality of audit results Keywords: Competence, Independence, Auditor Professional Skeptism and Audit Quality